2022
DOI: 10.1167/tvst.11.9.5
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Relationship Among Effective Lens Position, Predicted Refraction, and Corneal and Intraocular Lens Power in a Pseudophakic Eye Model

Abstract: Purpose To ascertain the theoretical impact of anatomical variations in the effective lens position (ELP) of the intraocular lens (IOL) in a thick lens eye model. The impact of optimization of IOL power formulas based on a single lens constant was also simulated. Methods A schematic eye model was designed and manipulated to reflect changes in the ELP while keeping the optical design of the IOL unchanged. Corresponding relationships among variations in ELP, postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…3,7 However, the "true" corneal power value is relevant in situations where we use the corneal power value to predict, for example, the appropriate intraocular lens power or to estimate the ocular magnification, and we then have to take care that the conversion from corneal front surface radius to corneal power matches the assumptions of the lens power formula. 23 Using current instruments, the geometry of the cornea can be measured including front and back surface curvature and corneal thickness. 7,24 However, we have to be aware that these measure optical path lengths and a conversion of the measurement data to CCT or Rp require the refractive index of the cornea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,7 However, the "true" corneal power value is relevant in situations where we use the corneal power value to predict, for example, the appropriate intraocular lens power or to estimate the ocular magnification, and we then have to take care that the conversion from corneal front surface radius to corneal power matches the assumptions of the lens power formula. 23 Using current instruments, the geometry of the cornea can be measured including front and back surface curvature and corneal thickness. 7,24 However, we have to be aware that these measure optical path lengths and a conversion of the measurement data to CCT or Rp require the refractive index of the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…However, this systematic backward shift of the intraocular lens away from the geometric lens position in the pseudophakic eye affects short eyes requiring high powered lens implants much more than long eyes with low powered implants. 23,24 As a consequence, short eyes with high powered lenses could end up with myopia, whereas long eyes with low powered lenses end up with hyperopia after cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that the magnitude of errors in IOL power prediction from ELP tend to be most significant for the SRK/T formula and least for the Hoffer Q formula [9]. This observation might explain why formulas that do not rely on corneal power in their ELP estimation, such as Haigis-L and Shammas, yield better results in LRS eyes [10,11].…”
Section: Sources Of Error In Intraocular Lens Power Calculations In P...mentioning
confidence: 99%
“…The 0.14 mm difference in AL may have resulted in a 1.03 D difference in spherical equivalent, which in combination with the effect of the effective lens position (0.20 D difference) neutralizes the myopic target deviation. 2 Tilt and decentration analyses (Casia2, Tomey Corp.) showed a tilt of 6.7 degrees at 191 degrees and a decentration of 0.29 mm at 164 degrees for the right eye. The IOL calculation of the left eye was adjusted for this myopic shift.…”
Section: Case Reportmentioning
confidence: 99%